DETERMINANTS OF THE OWN INCOME OF MUNICIPALITIES IN THE LUBUSKIE PROVINCE IN THE LIGHT OF THE RESULTS OF ECONOMETRIC MODELING - Szczuciński, Przemysław (Management and Administration Journal, 2022)
The local development of municipalities is a process taking place in a specific place and time. One of the most important measures of this process is the own income of municipalities, proceeding from the sources within the territory of a given local government. Their level depends to a large extent on internal determinants related to the nature of local economic activity. However, the impact of external and spatial determinants has to be taken into account as well. This paper reviews the literature dealing with determinants influencing the own income of municipalities and presents the results of an empirical case study of the Lubuskie Province. For the purpose of the study spatial econometric methods were used. On the basis of the data for 1999-2020, panel models of the own income of municipalities in the analysed region with spatial autoregression of the explained variable (SAR) and spatial autocorrelation of the random component (SE) were estimated. Both models were compared with the classical model estimated by the least squares method. The results of the research indicate the existence of a number of correlations between the own income of municipalities in the region, the examined explanatory variables and the spatial factor.